Leadership in Action the Right Start - A Team's First Meeting is key - Kanaga, Kim (Center for Creative Leadership, 2002)
A well-planned and well-executed first meeting is crucial to team success. It can create a sense of camaraderie, lay the groundwork on which team members build trust, and clarify the team's mission, goals, and processes.
Title from content provider
Keywords: Leadership; Teams in the workplace; Organizational behavior; Équipes de travail; Comportement organisationnel